مسؤولية محافظ الحسابات في كشف الغش والخطأ في القوائم المالية -دراسة ميدانية بالجزائر- - مداح, عبد الباسط; سعيدي, يحي (جامعة الوادي - University of Eloued, 2017)
هدفت الدراسة الى التعرف على مسؤولية محافظ الحسابات في كشف الغش والخطأ في القوائم المالية، وهذا من وجهة نظر محافظي الحسابات، ومن أجل تحقيق أهداف الدراسة تم تصميم استبيان وتوزيعه على عدد من المهنيين المزاولين للمهنة بالجزائر، حيث بلغ عدد أفراد العينة 54 فرد؛ وتوصلت الدراسة الى العديد من النتائج من بينها أن تقارير محافظ الحسابات تساهم بشكل كبير في الحد من الغش والخطأ، إضافة الى أن خبرة وكفاءة المدقق لها دور كبير في اكتشاف مختلف ممارسات الفساد المالي بصفة عامة والغش والخطأ بصفة خاصة بالمؤسسات الإقتصادية الجزائرية. The study aimed to identify the responsibility of the auditor in the detection of fraud and error in financial statements from the auditors’ perspective. In order to achieve the objectives of the study a questionnaire was designed and distributed to a number of professional practitioners in Algeria, where the number of respondents was 76 people The study came to many results, including tha the auditor’s reports contributed significantly to the reduction of fraud and error, in addition to the experience and efficiency of the auditor which play an important role in the discovery of the various practices of financial corruption in general and fraud and error in particular in Algeria economic institutions
The responsibility of the auditor in the detection of fraud and error in financial statements -A field study
مقال
Keywords: مسؤولية محافظ الحسابات، الغش، الخطأ، القوائم المالية.; responsibility of the auditor, fraud, error, the financial statements